Corporate Governance, Karakteristik Perusahaan dan Kinerja Perusahaan - Rahmat Setiawan; Ivone Dona Khoirun Nisa (Jurnal Bisnis dan Manajemen, 2021)
The purpose of this research is to determine and explain the influence of corporate governance and firm characteristics on firm performance. This research uses manufacturing companies as samples and the number of observations is 228. Multiple linear regression testing is used as a method for research. The results show that corporate governance proxied by proportion of independent commissioners, company characteristics proxied by leverage and company size shows that both simultaneously and partially have an effect on company performance